Strategies for adolescent health promotion developed by nurses (Research, Society and Development, 2022)
Objective: to identify and analyze the role of nurses in adolescent health promotion practices based on the scientific literature. Method: an integrative review carried out from March to April 2021. In the Scielo Brasil portal and in the BDENF database, the search equation “adolescent health” AND “health promotion' AND “nursing” was used, and in Lilacs, “teenager health” was used. adolescent” AND “nursing” AND “adolescence”. Results: 10 articles were included and from the analysis of these two categories emerged: Professional challenges for the development of adolescent health promotion in the scope of primary care and Strategies and practices to promote adolescent health. The main results were the lack of knowledge of nurses about the national guidelines for adolescent health care, the work overload in other health programs and the lack of adolescents seeking the unit, leading to the difficulty of approaching the nurse with the adolescent. Final Considerations: it was found that many nurses recognize the importance of promoting actions for the adolescent public in their area, but it was evident that many feel unprepared for this promotion. It is hoped that this study will help health professionals to seek effective promotion and prevention strategies aimed at the adolescent public.